TARI JARAN KEPANG BOYOLALI PADA PAGUYUBAN KETHOLENG DI KABUPATEN BOYOLALI (TINJAUAN BENTUK SAJIAN DAN GARAP TARI) - Widyawati Kedasih Putri; Silvester Pamardi (Institut Seni Indonesia Surakarta, 2020)
This study discusses the Boyolali Jaran Kepang dance at the Paguyuban Ketholeng in Boyolali Regency. The Boyolali Jaran Kepang dance was composed by Eko Wahyu Prihantoro. The problem taken in this research is, how the form of presentation and how to work on the Boyolali Jaran Kepang dance at the Paguyuban Ketholeng in Boyolali Regency. This research was conducted with a qualitative method using descriptive analysis and data collection techniques of observation, interviews, and literature study. Discusses these two problems, using concepts or thoughts from Slamet MD regarding the elements of dance formation which contain motion, rhythm, expression or taste, costumes, venues and dancers. Discussing the problem of working on using the concept of Rahayu Supanggah which contains material about the work on the event or the work on, working on, working on facilities, furniture or work on the device, determinants of work on and consideration of work on. The results of this study are describing the form of presentation and work on the Boyolali Jaran Kepang dance at the Paguyuban Ketholeng in Boyolali Regency. The Boyolali Jaran Kepang dance in its form of sajin is divided into 3 parts according to the dynamics of its movements. The makeup and clothing in this dance have a simple form and are easy to wear by dancers. The Boyolali Jaran Kepang dance accompaniment used a slendrobarreled accompaniment. In the preparation of the Boyolali Jaran Kepang dance, it is motivated by phenomena found in the Boyolali area. Boyolali Jaran Kepang dance has several elements in the dance work, namely choreographers, composers, dancers, musicians, costumes, movements, and the role of Boyolali Regency government.Keywords: Boyolali Jaran Kepang Dance, Ketholeng, form of presentation, working on dance.